Using Play as a Didactic Strategy to Enhance English Vocabulary Acquisition - Taimal Jimenez, Carmen Elizabeth (2025)
The purpose of this study was to design a guide of activities incorporating play as a teaching strategy to enhance English vocabulary development among elementary students at the César Antonio Mosquera Educational Unit during the 2024–2025 academic year. A convergent mixed-method approach was employed, using questionnaires, interviews, and field journals for data collection and analysis, followed by triangulation of the results. Based on the identified problem, a theoretical review was conducted to establish the fundamental characteristics that a didactic strategy based on play as a learning methodology should possess, tailored to the students’ specific needs and context. Quantitative data were analyzed through tabulation, while qualitative data were examined using NVivo software. The findings revealed that students have a limited English vocabulary and that, in some cases, current teaching methodologies fail to reinforce the words learned during the educational process.